DEVELOPMENT OF ASSESSMENT INSTRUMENTS BASED ON HOTS AT SURABAYA VOCATIONAL HIGH SCHOOL - Rudi Hartono; Triesninda Pahlevi (LPPM Universitas Negeri Jakarta, 2020)
This study aims to produce assessment instruments according to Higher Order Thinking Skills (HOTS) in General Administration subjects at Basic Competencies 3.9 The Implementation of Office Layout, and 3.10 The Implementation of Communication in the Workplace as many as 40 items of multiple-choice, and to decide the feasibility level of the questions in measuring students' HOTS based on the validation results from the material expert, evaluation expert, and linguist. This study is Research and Development (R&D) adapted Sugiyono's development model that has been adopted into 5 stages: potential and problems, data collection, product design, design validation, and design revision. Then, the research instruments used by the researcher were the validation sheet from the expert of material, evaluation, and the linguist. Furthermore, the validation result from the material expert was 98.3% (very strong). Besides, the validation result of the evaluation expert was 100% (very strong). Moreover, the validation results from the linguist were 98.7% (very strong). Therefore, the average validation result was 99% with the interpretations of criteria were